Effect of coal blending on arsenic and fine particles emission during coal combustion. (15th August 2021) - Zhao, Bo; Chen, Geng; Qin, Linbo; Han, Yuxin; Zhang, Qiang; Chen, Wangsheng; Han, Jun
Abstract: In this paper, the blending coal technology was proposed to control arsenic emission during coal combustion. The experimental results demonstrated that the blending coal could suppress the fine particles formation during coal combustion. Meanwhile, it was also found that arsenic mass size distribution was not consistent with particulate matter mass size distribution. Heshan (HS) and Huolinhe (HLH) coal were blended as the weight ratio of 50%:50% (named as HS1HLH1), the yield of 2.5–10, 1.0–2.5, 0.5–1.0 and 0.2–0.5 μm particles was reduced by 64.5%, 59.7%, 59.8% and 34.1%. Moreover, the blended coal was benefit to transfer arsenic in the fine particles to the coarse particles, and HS1HLH1 could reduce arsenic content in PM10 by 33%. It was regarded that two mechanisms accounted for the above phenomena: one mechanism was that the blended coals combustion decreased the ash fusion temperature, which promoted the reaction of Fe, Ca with aluminosilicates and suppressed the formation of the fine particles. Another was the interactions between the minerals and arsenic in coal, which could inhibit arsenic vaporization. Thus, arsenic vaporization-condensation process was cut, and arsenic in the fine particles was moved to the coarse particles.